PRODUCTION OF LACCASE BY FUNGI ISOLATED FROM SOIL VIA SUBMERGED FERMENTATION USING CORN COB AS SUBSTRATE - Nuhu, A.; Hussaini, Ibrahim; Gide, S.; Anas, G.; Madika, A. (FUDMA JOURNAL OF SCIENCES, 2020)
One of the limitations of large scale application of laccase (EC 1.10.3.2) is the inability to produce them in large quantity at an affordable cost. This study was carried out to screen indigenous fungi for their ability to produce laccase using the locally available substrate. Five soil samples were collected and diluted serially, 0.1 mL of the 10-5 and 10-6 dilutions were inoculated onto Potato dextrose agar (PDA) plates. The fungal isolates were identified based on their macroscopic and microscopic characteristics. The isolates were then screened for laccase production by growing them on PDA containing tannic acid as an indicator compound. The laccase producing isolates were further screened for their ability to utilize corn cob as a substrate for laccase production. Ten fungal species were isolated and identified as Trichoderma viridae (3), Trichoderma harzianum (3), Aspergillus niger (2), Fusarium sp. (1) and Penicillium sp. (1). Only two of the isolates namely T. viridae and T. harzianum were found to be laccase producers. Both laccase producing fungal species were able to utilize corn cob as substrate for laccase production. T. viridae had higher enzyme activity (2.228 U/mL) than T. harzianum (2.1583 U/mL) after 9 days of incubation. Laccase producing fungi were isolated in this study and they were able to use corn cob as substrate for laccase production.